Technical Guidance Preparation of the Education Unit Operational of the Kurikulum Merdeka for Teachers in Elementary Schools - Supriani, Yuli; Meliani, Fitri; Indah Wahyu Ningsing; Laila Maharani; Muhammad Agus Kurniawan (Institute of Education and Social Research, 2024)
This community service activity involving the IAI Agus Salim Metro Lampung PKM team aims to overcome obstacles for elementary school teachers in implementing the Independent Curriculum. This program provides benefits for various parties, including elementary school teachers at SDN 2 Sri Agung, SDN 2 Subing Karya, SDN 2 Ppurwosari, SDN 2 Srimulyo Anak Ratu Aji, and SDN 6 Tanjung Jaya, Central Lampung. The main obstacle faced by teachers in preparing the Operational Curriculum of Education Units in the Learning Curriculum is related to understanding concepts and their application in daily learning activities. Teachers need a comprehensive understanding of the preparation of the Operational Curriculum of Education Units with the Independent Learning Curriculum approach. The direction from the PKM Team makes an important contribution in delivering information, strategies, and approaches that support teachers to develop operational curricula effectively. Teachers in elementary schools who follow this technical guidance have experienced improved skills in developing operational curricula. This helps them to adapt the Merdeka Belajar Curriculum approach according to the characteristics and needs of students in their environment. Through a better understanding of the Merdeka Belajar Curriculum, teachers can design learning that is more contextual, relevant, and in accordance with student needs. This has the potential to improve the quality of education in Primary School, spark students' interest in learning, and improve their academic achievement.